Simulation of Single-layer Neural Networks - Didmanidze, Ibraim; Chachanidze, Guram; Kakhiani, Gregory (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The task of optimal management of artificial neuron network is represented. Showed that it is possible to use the Lagrange method with the help of the Lagrange new function for solving the task.